Causal Associations Between Tobacco, Alcohol Use and Risk of Infectious Diseases: A Mendelian Randomization Study - Hongxiang Zhu; Xiaohui Zhan; Congjie Wang; Yuying Deng; Xiaoping Li; Linru Song; Lingyan Zhao (Infectious Diseases and Therapy, 2023)
Abstract Introduction The causal effects of smoking and alcohol use on the risk of infectious diseases are unclear, and it is hard investigate them in an observational study due to the potential confounding factors. The aim of this study was to use Mendelian randomization (MR) techniques to assess the causalities between smoking, alcohol use and risk of infectious diseases. Methods Univariable and multivariable MR analyses were performed using genome-wide association data for the age of initiation of regular smoking (AgeSmk, N = 341,427), smoking initiation (SmkInit, N = 1,232,091), cigarettes per day (CigDay, N = 337,334), lifetime smoking (LifSmk, N = 462,690), drinks per week (DrnkWk, N = 941,280), sepsis (N = 486,484), pneumonia (N = 486,484), upper respiratory tract infection (URTI, N = 486,484) and urinary tract infection (UTI, N = 486,214) among individuals of European ancestry. Independent genetic variants that were significantly (P < 5 × 10−8) associated with each exposure were considered as instruments. The inverse-variance-weighted method was used in the primary analysis, which was followed by a series of sensitivity analyses. Results Genetically predicted SmkInit was associated with an increased risk of sepsis (OR 1.353, 95% CI 1.079–1.696, P = 0.009), pneumonia (OR 1.770, 95% CI 1.464–2.141, P = 3.8 × 10−9) and UTI (OR 1.445, 95% CI 1.184–1.764, P = 3 × 10−4). Moreover, genetically predicted CigDay was associated with a higher risk of sepsis (OR 1.403, 95% CI 1.037–1.898, P = 0.028) and pneumonia (OR 1.501, 95% CI 1.167–1.930, P = 0.00156). Furthermore, genetically predicted LifSmk was associated with an increased risk of sepsis (OR 2.200, 95% CI 1.583–3.057, P = 2.63 × 10−6), pneumonia (OR 3.462, 95% CI 2.798–4.285, P = 3.28 × 10−30), URTI (OR 2.523, 95% CI 1.315–4.841, P = 0.005) and UTI (OR 2.036, 95% CI 1.585–2.616, P = 3.0 × 10−8). However, there was no significant causal evidence for genetically predicted DrnkWk in sepsis, pneumonia, URTI or UTI. Multivariable MR analyses and sensitivity analyses showed that the above results for causal association estimations were robust. Conclusion In this MR study, we demonstrated the causal association between tobacco smoking and risk of infectious diseases. However, no evidence was found to support causality between alcohol use and the risk of infectious diseases.